Analysis of non-tuberculous mycobacteria types in high tuberculosis endemic areas - Na-na Li; Lu-lu Gao; Mei Liu; Wan-min Zhang; Xiao-ke Zhang; Ling Chen; Zhaojing Zong; Yuanbo Lan (Journal of Health, Population and Nutrition)
Abstract Background The incidence of non-tuberculous mycobacteria (NTM) has been rising globally, posing significant challenges for diagnosis and treatment, particularly in regions with high tuberculosis (TB) incidence. This study aims to investigate the epidemiological, demographic, and clinical characteristics of non-tuberculous mycobacterial lung disease (NTM-PD) in areas with a high incidence of TB. Method This study was conducted at the Affiliated Hospital of Zunyi Medical University from January 2017 to December 2021. A total of 6259 culture-positive specimens were analyzed. Screening was based on acid-fast staining, colony morphology, and p-nitrobenzoic acid detection, which identified 107 suspected NTM strains. Gene sequencing confirmed 51 NTM-positive cases. Results The predominant species identified were Mycobacterium abscessus (33.33%) and Mycobacterium intracellulare (27.45%). Several risk factors were associated with higher susceptibility to NTM-PD suspect, including bronchiectasis, low serum albumin levels (< 3.5 g/L), and male gender. The study found that although the isolation rate of NTM remained stable over the five-year period, drug resistance rates for the dominant species were notably high. Conclusions The findings highlight the need for clinicians in TB-endemic areas to carefully distinguish NTM infections from TB. The stable isolation rates of NTM, coupled with the high drug resistance of key species, underscore the importance of accurate diagnosis and tailored treatment strategies to manage NTM-PD effectively.